Débat - Sales, Arnaud; Bélanger, Gérard; Séguin, Normand; Ouellet, Fernand; Savard, Pierre; David, Hélène; Delage, Denys; Desaulniers, Jean-Pierre; Paquet, Gilles; Sales, Arnaud; Niosi, Jorge (Recherches sociographiques)

(untitled) (Département de sociologie, Faculté des sciences sociales, Université Laval, 1985)
Débat